Characterization Of Durability And Mechanical Properties Of ‘Cocos Nucifera Linn’ Fibre (Cnf) Reinforced Foamcrete And Its Performance At Elevated Temperatures - Zamzani, Nabihah Mohd (2019)
The call for lightweight foamcrete technology is impelled by the amplified rules and guidelines with the aim of minimizing greenhouse gas emission and reducing carbon footprint. The use of natural fibres in foamcrete is considered as a useful option in making concrete as a sustainable material. Therefore, the aim of the present study is to characterize the durability and mechanical properties of foamcrete reinforced with cocos nucifera linn fibres (CNF) as well as its performance at elevated temperatures. CNF refer to agricultural waste or by-products that can be obtained through the distribution of coconut oil and can be accumulated in a large amount in Malaysia. This study aimed to identify the response of CNF towards six different contents (0.1%, 0.2%, 0.3%, 0.4%, 0.5%, and 0.6%) by mix volume. Three different densities of 650, 1050 and 1450 kg/m3 were tested in this study. The proportion of foamcrete was cement, sand, and water which were represented by the ratio of 1:1.5:0.45. Results showed that, CNF plays a vital role to improve the durability properties such as water absorption, porosity, drying shrinkage, carbonation depth and ultrasonic pulse velocity of foamcrete. Addition of CNF also had enhanced the compressive, flexural and splitting tensile strengths of foamcrete. CNF acts as an anti-micro crack agent by preventing cracks from forming on the foamcrete.